itamin A Orange sweet potato and Iron beans grown and consumed respectively by 960,000 and 695,000 households in Uganda - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
2020 marked 15 years of HarvestPlus activities in Uganda. The latest monitoring data shows that 960,000 smallholder households – more than 10% of the Ugandan population – were growing vitamin A orange sweet potato (OSP) varieties and 695,000 households were growing iron beans. Ensuring the supply of clean planting material, payback and pay forward delivery systems, digital technologies, and a multi-stakeholder technical working group are some of the innovative approaches that have been used successfully to sustain and scale-up biofortification.